Shedding Light on Indonesian Islam: The Latest Trends from Europe - Fadlan, Muhammad Nida' (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
On December 13, 2024, the Institute for Languages and Cultures of the Islamicate World at the University of Cologne held the “Indonesian Studies Day 2024” in Cologne, Germany. Chaired by Prof. Dr. Edwin P. Wieringa (Professor of Indonesian Philology, University of Cologne) and co-chaired by Muhammad Nida’ Fadlan (PhD researcher in Indonesian Islamic Philology, University of Cologne), this academic event focused on the intersection of religion, culture, and identity within the context of Islam in Indonesia. It served as a colloquium that gathered Indonesian PhD students in Europe to discuss the latest research on this subject. There were two main reasons for this event. First, Indonesia is a country that is globally still unfamiliar to many people, even though it has the largest population of Muslims in the world. The attempts to showcase the rich Islamic heritage of Indonesia have not yet been very successful. Second and relatedly, there is still a need to promote academic activities related to Indonesian Islamic studies. This forum brought together doctoral students from different European universities who are researching various topics related to Indonesian Islam, enabling profound and fruitful discussions. By coming together, this intellectual gathering encourages and furthers research in this area.